IMPROVING STUDENTS’ COLLABORATION SKILLS AS TEACHER CANDIDATES THROUGH LESSON STUDY-BASED JiRQA LEARNING STRATEGY - Saparuddin, .; Prasetyo, Triastono Imam; Mahanal, Susriyati (PEOPLE: International Journal of Social Sciences, 2018)
The learning process of School-Based Management course by emphasizing collaboration skill is an effort to develop teacher candidates’ character which can be implemented at school. Lesson study-based Classroom Action Research (CAR) was conducted on School-Based Management course for undergraduate students of Biology Education Department at Universitas Negeri Malang. The learning strategy of Jigsaw combined with Read Question Answer (JiRQA) was implemented to improve students’ collaboration skill. The action research was conducted in two cycles in which each cycle consists of 4 stages; i.e. planning, implementation, observation and reflection. The implementation stage was carried out following the steps of lesson study; plan, do and see (reflection). Meanwhile, the observation of the learning process and questionnaire at the end of each cycle were carried out to determine the students’ collaboration skill. The average of students’ collaboration skill in cycle I is 75.44% (good), while in cycle II is 80,69% (very good). The result of the students’ collaboration skill in both cycle I and cycle II indicates that JiRQA learning strategy can enhance the students’ collaboration skill in learning School-Based Management course.